Movement disorders in hereditary spastic paraplegias - Jose Luiz Pedroso; Thiago Cardoso Vale; Julian Letícia de Freitas; Filipe Miranda Milagres Araújo; Alex Tiburtino Meira; Pedro Braga Neto; Marcondes C. França; Vitor Tumas; Hélio A. G. Teive; Orlando G. P. Barsottini (Arquivos de Neuro-Psiquiatria)
Background Hereditary or familial spastic paraplegias (SPG) comprise a group of genetically and phenotypically heterogeneous diseases characterized by progressive degeneration of the corticospinal tracts. The complicated forms evolve with other various neurological signs and symptoms, including movement disorders and ataxia.